El papel del poliéter éter cetona (peek) en la confección de prótesis parcial removible mediante sistema cad cam - Jerez Muzo, Danilo Alexander (2025)
Polyether Ether Ketone is particularly used in metal-free restorations, such as removable partial dentures, due to its excellent biocompatibility, tensile strength, and aesthetic properties that resemble dentin. Unlike traditional metallic materials, PEEK not only avoids clinical problems such as allergies but also improves patient comfort thanks to its lightness and lack of metallic taste. Additionally, CAD/CAM technology allows the design and fabrication of highly precise, customized dentures. Objective: To determine the viability of polyether ether ketone by analyzing its properties and benefits as a removable partial denture. Materials and Methods: A qualitative research study was made to analyze information from indexed journals with a high publication quartile, using the PRISMA method. Information was obtained from databases such as Google Scholar, PubMed, Scielo, and ProQuest from the last five years. Thereby, collecting valid information according to inclusion and exclusion criteria, where the use of PEEK in removable partial dentures using the CAD/CAM system is used. Results: A total of 41 articles were found, of which 12 were selected for the study after excluding documents because they were duplicated, non-recoverable documents. PEEK as bridge for fixed prostheses, other types of studies, publication date, and lack of relevance to the topic. Among the most relevant findings were PEEK as an alternative to metal ingredients in the mouth and the role of polyether ether ketone in dentistry. Conclusions: PEEK is a biocompatible material with favorable properties that allow its use in restorative dentistry for various treatment options and applications. Research data shows positive results regarding its use with the CAD/CAM system.